In the Heat of Africa's Underdevelopment : Africa at the Crossroads -Time to Deliver - Forje, John W. (Book collections on Project MUSE., 2019)
The ever growing disparity in living standards between the developed and developing polities constitutes a striking feature of life on Planet Earth. This publication is an attempt to highlight some of the factors dividing the worlds apart. A new North-South synergy is needed in creating a balanced world at peace with itself. As long as more than half-the population of the world go to bed hungry there can be no peace. A sting rich world and a sting poor world cannot cohabit peacefully. How to build a more equitable and balanced world is the challenge facing us. We need to embrace and practice our long-aged concepts of 'ubuntu', 'harambee' and 'batho pele' among others in creating, and consolidating the new world order. Africa is underdeveloped. It requires serious structural modification in our current mindset, thinking and actions which calls for total involvement of every citizen. The ideas advanced in this book are strategies and pathways for dealing with the problems of poverty, corruption, the distribution of power, deterrence, good governance, health, human capacity building and the challenge of bringing about a systemic structural-functional governance construct for the African continent.